Covid-19: perception of population risk and compliance with protection measures in Havana - Juan Rubén Herrera Masó; Luisa Hernández Alarcón; Carlos L. Pérez Hernández; Gisselle Fernández Peña; Alain Manuel Chaple Gil; Ernesto B. Rodríguez Ledesma; Nidia Márquez Morales (Universidad de Ciencias Médicas de La Habana, 2022)
Introduction: Before cases of Covid-19 were registered in Cuba, a prevention and control plan was developed and a working group was formed to advise the Government on the confrontation of the pandemic with a crucial and cohesive participation of the community, the health workers, and the scientific community of the country. Objective: to explore the risk perception and attitudes of people residing in Havana in compliance with protection measures during Covid-19. Material and Methods: A cross-sectional descriptive study was carried out between May and July 2021 applying an online survey in Google Forms that remained online for three months and was answered voluntarily by 2 012 residents in all the municipalities of Havana that were members of population groups of interest on Telegram®, WhatsApp, and other social networks. Results: Low risk perception and non-compliance with protection measures were evidenced among the respondents. Conclusions: The low perception of population risk and non-compliance with protection measures contribute to increasing the severity of the epidemiological situation in Havana and the spread of the pandemic.